Variability of the runoff coefficient for selected catchments in the upper Vistula river catchment - Katarzyna Baran-Gurgul; Marek Bodziony; Katarzyna Kołodziejczyk (Acta Scientiarum Polonorum. Formatio Circumiectus)
The runoff coefficient is one of the basic hydrological characteristics of the catchment. It can be determined using multiannual, periodic, or annual data measurement sequences. The variability of the runoff coefficient can be influenced by the terrain, the land cover, and the land-use in the catchment, among other things. The present study is an attempt to analyse changes in the runoff coefficient over a period of 30 years (1984–2013) for 49 gauging sections located in the Carpathian part of the Upper Vistula catchment. An additional analysis was carried out to study the impact of changes in the land cover and land-use of the catchment on the value of the runoff coefficient. Rainfall and daily flows data was made available by IMGW-PIB, whereas land cover and land-use data of the catchment come from the CORINE Land Cover system (1990, 2000, 2000, and 2012).